Polygamy in Islamic Context: A Qualitative Analysis of Perspectives and Realities among Persis Women - Nurul Irfan (UIN Sunan Gunung Djati Bandung, 2023)
This research aims to comprehensively explore the following aspects: (1) the conceptual frameworks employed by Persis scholars in their understanding of polygamy from the perspective of Persis women; (2) the subjective interpretations and meanings of polygamy among Persis women; and (3) the empirical realities and experiences of religious practice among Persis women regarding polygamy. The study adopts a qualitative research approach, utilizing socio-phenomenological methods, specifically drawing upon symbolic interactionism theory and social construction theory within the Bergerian sociology of knowledge, as the analytical framework. The research findings reveal significant variations in the perspectives of Persis scholars regarding the doctrine of polygamy. These divergences can be attributed to differences in educational backgrounds among Persis scholars (asatidz). Central to the debates are interpretations of justice within the context of polygamy, the criteria for engaging in polygamous marriages, the understanding of the permissible number of wives, and the interpretations of scriptural verses related to polygamy, whether regarded as mutasyabihat (ambiguous) or muhkamat (clear). In terms of the understanding of polygamy among Persis women, socio-cultural factors play a significant role, resulting in a context where Persis women in Garut perceive themselves as equal to men. Consequently, they assert their personal rejection of polygamy, while simultaneously recognizing its permissibility within the framework of Islamic teachings. In practice, instances of polygamous marriages among Persis women are rare, primarily due to the perception that the requirements for polygamy are nearly unattainable (suprahumanization of polygamy